Hydroxyapatite-titania nanotube composite as a coating layer on cobalt-chromium based implant material - Mostafa Rezazadeh Shirdar, 1984-, author 522172; Izman Sudin, supervisor 618549; Mohammed Rafiq Abdul Kadir, supervisor 602938; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Kejuruteraan Mekanikal))